2009
DOI: 10.1074/jbc.m109.035568
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-stimulated Phosphorylation of the Rab GTPase-activating Protein TBC1D1 Regulates GLUT4 Translocation

Abstract: Insulin stimulates the translocation of the glucose transporter GLUT4 from intracellular locations to the plasma membrane in adipose and muscle cells. Prior studies have shown that Akt phosphorylation of the Rab GTPase-activating protein, AS160 (160-kDa Akt substrate; also known as TBC1D4), triggers GLUT4 translocation, most likely by suppressing its Rab GTPase-activating protein activity. However, the regulation of a very similar protein, TBC1D1 (TBC domain family, member 1), which is mainly found in muscle, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
67
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(74 citation statements)
references
References 26 publications
(46 reference statements)
5
67
2
Order By: Relevance
“…Consistent with a previous study (27), we found that adenovirus-mediated expression of TBC1D1 did not affect insulin-evoked Akt phosphorylation (data not shown) but led to a significant inhibition of insulinstimulated glucose uptake compared with cells expressing luciferase control (Fig. 5F).…”
Section: Tbc1d1 Is An Interacting Partner and Downstream Effector Of supporting
confidence: 80%
See 3 more Smart Citations
“…Consistent with a previous study (27), we found that adenovirus-mediated expression of TBC1D1 did not affect insulin-evoked Akt phosphorylation (data not shown) but led to a significant inhibition of insulinstimulated glucose uptake compared with cells expressing luciferase control (Fig. 5F).…”
Section: Tbc1d1 Is An Interacting Partner and Downstream Effector Of supporting
confidence: 80%
“…Of note, a previous study showed that Ser-229 of mouse TBC1D1 (equivalent to Ser-235 on human TBC1D1) within this region is potentially phosphorylated by Akt (27). We confirmed that insulin stimulated TBC1D1 phosphorylation at Ser-235 in a time-dependent manner in both EDL muscle of C57 mice and C2C12 myotubes (Fig.…”
Section: Tbc1d1 Is An Interacting Partner and Downstream Effector Of supporting
confidence: 76%
See 2 more Smart Citations
“…It is worth noting that a close homolog of AS160, Rab GAP TBC1D1, was reported to function in GLUT4 translocation in adipocytes ( 47 ) and muscle cells ( 48 ). This homolog has substrate specifi city similar to that of AS160 ( 49 ) and could also be involved in CD36 traffi cking.…”
Section: As160 and Rab8a Regulate Membrane Recruitment Of Cd36mentioning
confidence: 99%